La propriété intellectuelle : nouvelles formes et nouveaux enjeux - Vivant, Michel (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2018)
La propriété intellectuelle n’est pas intangible. Née dans un certain contexte culturel, le XVIIIe siècle occidental pour simplifi er, elle est trop souvent conçue de manière dogmatique. L’analyse économique dominante y voit un mécanisme d’incitation à la création. Mais elle se laisse mal enfermer dans des schémas simples. Etroitement liée au marché, elle permet de réserver au titulaire des droits une portion de celui-ci en l’assurant d’un monopole juridique que l’on peut ou non analyser comme une propriété. Mais, propriété ou non, l’instrument qu’elle est fait l’objet de nouveaux usages, spécialement à travers des figures comme les Creative Commons qui ne cherchent plus à écarter les tiers. Des objets inhabituels aussi différents que les savoirs traditionnels ou les produits de l’intelligence artifi cielle viennent encor bousculer les schémas reçus. La propriété intellectuelle doit faire l’objet d’une réfl exion politique au vrai sens du terme. Intellectual Property at Stake: New Forms and New Debates Developing nations are characterized by the absence of much-needed institutional arrangements to regulate market exchange, mobilize economic resources, coordinate policy implementations, and administer developmental programmes. Successful economic development depends to a large extent on whether such institutional voids can be fi lled in one way or another. Using China as an exemplary case, this paper looks at how institutional voids are fi lled by unconventional actors/organizations who, in the process of negotiating rules, resources, and discourses with formal and informal circuits of power, contribute to the emergence of alternative forms of governance. By focusing on the case of private sector fi nancing, the paper documents a succession of creative efforts to remedy a malfunctioning aspect of the fi nancial system, leading to such innovative creations as pawnshops, informal investment consortia, consignment shops, capital management corporations, or crowdfunding. The source of institutional entrepreneurship derives not solely from the private sector, but also from central and local state actors. Furthermore, the paper argues that the broader socio-political structures play a gatekeeping role in institutional selection. The successful institutionalization of a new practice depends very much on its clash and mesh with the broader socio-political structures.